1991
DOI: 10.2105/ajph.81.7.908
|View full text |Cite
|
Sign up to set email alerts
|

Television viewing and obesity in adult females.

Abstract: We measured the relation between time spent watching television per week and obesity in 4,771 adult females. After controlling for age, education, cigarette smoking, length of work week, and weekly duration of exercise, females who reported three to four hours of TV viewing per day showed almost twice the prevalence of obesity (body fat greater than 30 percent), and those who reported more than four hours of TV watching per day showed more than double the prevalence of obesity, compared to the reference group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
97
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(105 citation statements)
references
References 11 publications
7
97
0
Order By: Relevance
“…24 However in this study the relationship between television viewing and overweight was modi®ed by physical activity; a ®nding consistent with other cross-sectional studies that have found physical activity or physical ®tness to modify this relationship. 21,22 Our study has produced mixed results, in that there was a lack of a clear relationship between overweight and television viewing for the most sedentary category but a relationship appeared to exist for other activity categories. This suggests that some active people may compensate for their participation in physical activity by increased nutritional intake or increased sedentary periods in other parts of their day.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…24 However in this study the relationship between television viewing and overweight was modi®ed by physical activity; a ®nding consistent with other cross-sectional studies that have found physical activity or physical ®tness to modify this relationship. 21,22 Our study has produced mixed results, in that there was a lack of a clear relationship between overweight and television viewing for the most sedentary category but a relationship appeared to exist for other activity categories. This suggests that some active people may compensate for their participation in physical activity by increased nutritional intake or increased sedentary periods in other parts of their day.…”
Section: Discussionmentioning
confidence: 78%
“…9±12,14,16,17,20 Fewer studies have examined the relationship between overweight and obesity, television viewing, and physical activity in adults. One study of adult males 21 and another of adult females, 22 found signi®-cant positive associations between body fat percentage and hours of television viewing. A positive association between television viewing and BMI was reported among adult Pima Indians, together with a negative relationship between television viewing and physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…There are at least 2 explanations for the observed positive association between TV watching and diabetes risk. First, TV watching is directly related to obesity and weight gain, [11][12][13][14][15]33 probably due to lower energy expenditure (ie, less physical activity) and higher caloric intake. Second, participants who spent more time watching TV tended to eat more red meat, processed meat, snacks, refined grains, and sweets and fewer vegetables, fruits, and whole grains.…”
Section: Commentmentioning
confidence: 99%
“…A sizeable body of cross-sectional and prospective evidence suggests that sedentary behavior and physical activity are independently associated with BMI in adults. [20][21][22][23][24] In fact, research has found relatively low correlations between time spent in physical activity and sedentary behavior. 24,25 However, it is unclear whether the strength of the association between sedentary behavior and BMI varies according to time spent in physical activity, or vice versa.…”
Section: Introductionmentioning
confidence: 99%